Copper-Catalyzed Aerobic Methyl/Methylene Oxygenation and C–H Formylation with a DABCO–DMSO System for the Synthesis of Carbonyl Indoles and Pyrroles - Wang, Yi-Feng; Zhang, Feng-Lian; Chiba, Shunsuke (Synthesis, 2012)
Copper-catalyzed aerobic methyl/methylene oxygenation of substituted indoles and pyrroles was developed using 1,4-diazabicyclo[2.2.2]octane (DABCO) as an additive in dimethyl sulfoxide (DMSO). Similar aerobic catalytic conditions could also be utilized for direct C–H formylation of C(3) on indoles and C(2) on pyrroles.
Keywords: aldehydes; copper; oxygen; oxygenation; formylation